AB0598 THE INCREASING USE OF IMMUNOSUPPRESSANTS IN EARLY SYSTEMIC SCLEROSIS. (2nd June 2020) - Park, R.; Nevskaya, T.; Baron, M.; Pope, J.
Abstract : Background: Immunosuppression (IS) remains the main treatment for progressing skin involvement, active interstitial lung disease (ILD) and underlying inflammatory joint (IJ) or muscle disease in systemic sclerosis (SSc). Objectives: This study investigated the pattern and trends in immunosuppressive agent use in patients with early SSc diagnosed before and after 2007 to determine whether the changes in the preferred type and combination of IS, timing and predictors of administration took place over the past decade. Methods: 397 SSc patients from Canadian Scleroderma Research Group (CSRG) database (183dcSSc, 214 lcSSc) who had baseline and follow-up visits within 3 years (1.8±0.8) after disease onset were included: 82% females, age at diagnosis 53±13 years, disease duration 1.6±0.8 years. Organ involvement was assessed by modified Rodnan skin score, Medsger Disease Severity Score (DSS) and CSRG definitions using bivariate, chi-squared, ANOVA, and adjusted regression analyses. Results: 115 dcSSc patients (63%) and 62 lcSSc (29%) received IS, most commonly methotrexate (MTX) (72% dcSSc and 52% lcSSc), followed by mycophenylate mofetil (MMF) and cyclophosphamide (CYC). Within the patients receiving IS, monotherapy prevailed (77% dcSSc and 68% lcSSc); CYC and azathioprine were the preferred choice of IS more frequently in lcSSc compared to dcSSc (p<0.006 and p<0.02, respectively). In dcSSc, IS were predominantly prescribed at years 2 and 3 after the onset of first non-Raynaud's phenomenon (RP) manifestation, when about half of the patients received IS. The proportion of lcSSc patients receiving IS was significantly lower and distributed more equally through the first three years. After 2007, dcSSc patients received IS more often (74% vs 50%, p=0.001), especially MTX (p=0.02) and MMF (p<0.05), and earlier (peaked at 2 years after disease onset)(Table 1 ). IS administration was associated with male gender, ILD, a-Scl-70 positivity, ACA-negativity and IJ disease in lcSSc, and with ACA-negativity and a higher mRSS in dcSSc. Multivariate logistic regression analysis showed that IS treatment could be predicted by ACA-negativity in lcSSc patients (Exp(B) 0.317, p=0.012) and younger age in dcSSc patients (Exp(B) 0.974, p=0.002). Conclusion: Over the past decade, there has been a trend to prescribe IS more often, especially MTX, and earlier in dcSSc patients. MMF has gained favour over CYC. Autoantibody status was the most consistent predictor whether a patient is likely to take IS over the course of the disease. Disclosure of Interests: Ryan Park: None declared, Tatiana Nevskaya: None declared, Murray Baron: None declared, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB